The Level of Health Literacy in World and Turkey and Affecting Factors - Avcı, Emine; Özkan, Seçil (Turkey Health Literacy Journal, 2020)
The World Health Organization (WHO) defines health literacy as the capacity of cognitive and social skills necessary to access, understand and use information about health in order to maintain and improve good health of individuals. Inadequate levels of health literacy can lead to difficulties in understanding information and messages related to health, less use of preventive health services by individuals, problems with access to health services, increased use of emergency services, higher level of illness of individuals, increased incidence of chronic diseases and hospital admissions. Many sectors are in charge of improving health literacy as well as health service providers and health service providers.
Keywords: Health Literacy; Public Health.